THE ROLE OF INTERNATIONAL FINANCIAL INSTITUTIONS IN ECONOMIC DEVELOPMENT - Shaxnoza Atakuzieva (Ecominds Press, 2025)
International financial institutions (IFIs) play a crucial role in fostering economic development by providing financial assistance, technical expertise, and policy recommendations to countries worldwide. These institutions, including the International Monetary Fund (IMF), the World Bank, and regional development banks, contribute to economic stability, infrastructure development, and financial sector reforms. In Uzbekistan, IFIs have been instrumental in supporting economic modernization, facilitating foreign investment, and implementing financial sector reforms. This study examines the impact of IFIs on economic development, focusing on their role in financing large-scale projects, improving governance structures, and enhancing financial stability. The research highlights both the benefits and challenges associated with IFI involvement, such as conditional financial aid, policy recommendations, and the effectiveness of their assistance in different economic contexts. By analyzing global experiences and Uzbekistan’s engagement with IFIs, this study provides insights into optimizing international financial cooperation for sustainable economic growth.
Keywords: International financial institutions, economic development, financial stability, IMF, World Bank, foreign investment, infrastructure financing, financial sector reforms, Uzbekistan, global economy.